A STRUCTURE OF KNOWLEDGE AS A PRECEDENT TEXT FOR A PARODY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
According to the theory of intertextuality, elaborated by Julia Kristeva, every text, including literary ones, refers to another – precedent – text(s). Intertextual links may have various forms and include parody among others. Intertextuality has been usually considered in the framework of literary studies. Thus, this article suggests presenting the precedent text as a cognitive structure of knowledge which can be recognized with the help of parody. On the example of allusive texts from the stories of the Glass Family Series by J. D. Salinger, the author explores and demonstrates the mechanism of cognitive structure recognition, and comes to the conclusion that parody is being used as means of activating of cognitive structure of knowledge.